Transforming Governance to Implementation Foreign Loan-Funded Activities in BMKG for Good Governance - Fadhoni, Yusuf (Center for Maritime Policy Governance Studies (CMPGS), 2025)
Indonesia’s archipelagic geography makes maritime transport, fisheries, offshore works, and coastal livelihoods highly exposed to rapidly changing hydro-meteorological hazards, so marine meteorological services function as critical decision infrastructure rather than merely forecast products. This study examines the governance-to-implementation gap in BMKG’s Marine Meteorological System Phase II (MMS-2), a technology-intensive modernization program financed by an AFD external loan (€63.7 million) that experienced an extreme implementation lag of around 4.5–5 years, delaying service benefits and increasing fiscal exposure. Using a qualitative single-case design, the research relies on documentary evidence (planning/design artefacts, implementation records, and legal–procedural frameworks) to reconstruct the end-to-end implementation timeline, identify decision choke points, map causal chains through Fault Tree Analysis (FTA), and derive improvement options via the SOAR framework integrated with top-down/bottom-up implementation logics. Findings show the dominant bottleneck was low governance throughput slow, uncertain decision-making that stalled procurement and delivery driven by mutually reinforcing factors: early planning immaturity, regulatory deadlock between national procurement requirements (including TKDN/local content) and lender No Objection procedures, and legal shifts linked to the CFA amendment. Although acceleration emerged after the first drawdown (March 2025), persistent risks remained in fiscal data accountability and late-stage integration under a compressed catch-up corridor to 2028. The study concludes that a two-track “Agile Governance” strategy permanent cross-agency steering plus an autonomous joint task force with harmonized technical–procedural guidance and strengthened data integrity can accelerate delivery while preserving transparency and auditability.